Pengaruh Keputusan Investasi dan Modal Intelektual terhadap Nilai Perusahaan dengan Ukuran Perusahaan sebagai Pemoderasi - Veronika Maria Christianti; Dea Annisa (Jurnal Mahasiswa Manajemen dan Akuntansi, 2026)
This study aims to examine and obtain empirical evidence regarding the effect of investments decisions and intellectual capital on firm value with company size as a moderating variable in financials companies listed on Indonesia Stock Exchange in 2022 – 2024. The research sample collection technique used a purposive sampling method, resulting in a sample of 73 companies with a total of 219 observations of data and using an associative quantitative approach. The data analysis technique used is panel data regression, with data processing using E views 12 program. The results of the research show that the investments decisions have an effect on firm value, intellectual capital no have an effect on firm value, company size is able to moderate the effect of investments decisions on the firm value and company size is not able to moderate the effect of intellectual capital on the firm value. This study provides insight into the importance of investment decisions in increasing company value amidst economic challenges.